THE STRESS-STRAIN STATE OF ELASTIC HALF-SPACE LOADED BY UNIFORMLY DISTRIBUTED LOAD OVER THE AREA OF THE RECTANGLE AND THE INFINITE STRIP - I. K. Badalakha (Nauka ta progres transportu, 2009)
The article shows the result of solving the problem on the stressed-and-strained state of an elastic semi-space because of the load action, which is uniformly distributed over the strip of constantly width and final or infinite length, with the use of non-traditional linear dependence of strains on the stressed state that differs from the generalized Hooke’s law.